2007
DOI: 10.4161/cc.6.10.4244
|View full text |Cite
|
Sign up to set email alerts
|

Daxx Shortens Mitotic Arrest Caused by Paclitaxel

Abstract: Resistance to the anti-neoplastic drug paclitaxel is frequent in breast cancer patients. Most studies of paclitaxel resistance have focused on pathways that elicit cellular response, while little is known about players involved in the acquirement of taxane resistance. By screening a cohort of breast cancer cell lines, we observed a correlation between level of protein Daxx and response to paclitaxel. Cells lines expressing increased level of Daxx displayed a robust paclitaxel response with nearly all cells und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…Recent report described HGF-induced repression of Daxx in breast epithelial cells (Leroy et al, 2006); thus, upregulation of c-met by HGF (Seol et al, 2000) may combine activation of c-met promoter by HGF and repression of Daxx. Daxx level was recently found as an important factor that determines proper response to the chemotherapeutic agent paclitaxel (Lindsay et al, 2007); thus, cells with low level of Daxx not only express increased c-met and are more metastatic-prompted, but also can be resistant to the taxol therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent report described HGF-induced repression of Daxx in breast epithelial cells (Leroy et al, 2006); thus, upregulation of c-met by HGF (Seol et al, 2000) may combine activation of c-met promoter by HGF and repression of Daxx. Daxx level was recently found as an important factor that determines proper response to the chemotherapeutic agent paclitaxel (Lindsay et al, 2007); thus, cells with low level of Daxx not only express increased c-met and are more metastatic-prompted, but also can be resistant to the taxol therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Daxx protein participates in mitosis regulation, thus affecting taxane resistance. 20,21 According to our model, 21 Daxx-deficient cells cannot resolve prometaphase/ metaphase transition as efficiently as control cells. This would explain the observation that, upon taxane treatment, cells with a low Daxx expression are protected from mitotic catastrophe/slippage and are able to complete mitosis and survive after taxane decay.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, experimental downregulation of USP7 reduced sensitivity to Taxol treatment in HEp2 cells, as previously shown for Daxx. 20,21 As Aurora-A overexpression correlates with poor patient outcome 43 and resistance to taxanes, 17 Aurora-A inhibitors have been developed for clinical application. Currently, MLN8054, a selective inhibitor of Aurora-A, 44 is in phase I clinical trials in patients with advanced malignancies and solid tumors including breast cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations